The Electronic Organ and the Flux and Embedding of Chinese Music in the Digital Era (Journal of Interdisciplinary Insights, 2025)
This study examines the transformative role of the electronic organ in mediating the flux (circulation) and embedding (contextualization) of traditional Chinese music in the digital era. Through ethnographic research, case studies of original adaptations, and pedagogical analysis, the dissertation argues that digital technologies like the electronic organ enable traditional music to transcend spatial and temporal boundaries while retaining cultural significance. The research identifies three critical processes: (1) timbral translation, where folk instrument sounds are reconfigured for digital interfaces; (2) structural recalibration, where ritual narratives adapt to concert and online formats; and (3) participatory re-embedding, where audiences co-construct meaning across physical and virtual spaces. Findings reveal that successful revitalization hinges on balancing technological innovation with ethical fidelity to cultural roots—a framework termed interpretive reconstruction. By demonstrating how the electronic organ facilitates both global dissemination and localized resonance, this study redefines digital traditional music not as preservation or disruption, but as an evolving dialogue between heritage and modernity.
Keywords: Electronic organ; traditional Chinese music; digital heritage; flux and embedding; cultural revitalization